Study on the supramolecular interaction of inclision complex of β - Cyclodextrin with dithizone and dithizone-zinc and its analytical application / Siti Nurur Raihan Mohd Kamal - Siti Nurur Raihan, Mohd Kamal (2011)
The non-covalent interaction of beta-cyclodextrin (β-CD), dithizone (H2Dz) and dithizone-zinc (H2Dz-Zn) complex was studied in detail. Solid samples were studied using solid state 13C Cross Polarization and Magic Angle Spinning spectroscopy (13C CP/MAS NMR), Fourier Transform Infrared spectroscopy (FTIR), Thermal Gravimetric Analysis (TGA), Differential Scanning Calorimetry (DSC), Powder X-Ray Diffraction (XRD) and Energy Dispersive X-ray (EDX) to investigate the formation of the inclusion complex. Spectrophotometric technique was also used to assess the formation of inclusion complex in liquid form. The characterization results supported the formation of inclusion complex. The results showed that β-CD formed a complex with H2Dz in a ratio of 2:1 and with H2Dz-Zn in a ratio of 1:1. A spectrophotometry method was developed based on the enhancement of the absorbance of dithizone-zinc complex produced through complex formation in the presence of β-CD. A linear relationship between absorbance and concentration of zinc was obtained in the range of 0.1 – 9.0 mg/L with correlation coefficient of 0.996. The detection limit obtained was 0.005 mg/L and the relative standard deviation (R.S.D) was 2.05%. The developed method was applied in real samples and the recoveries obtained were from 85 – 95%.